2017
DOI: 10.1080/14992027.2017.1303200
|View full text |Cite
|
Sign up to set email alerts
|

The development of the University of Jordan word recognition test

Abstract: In general, the current study was successful in producing recorded speech materials for Jordanian Arabic population. This suggests that the speech stimuli generated by this study are suitable for measuring speech recognition in Jordanian Arabic-speaking listeners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…The intensity at which the average score across listeners and lists was 50% was 11.64 dB above their PTA for the Afrikaans lists. The performance-intensity slope of the Afrikaans lists is similar to slope values reported for monosyllabic word lists in other languages, such as 2.8-4.2 %/dB for Spanish (Flores & Aoyama, 2008), 4.1 and 3.47%/dB for Mandarin (Han et al, 2009;Wu et al, 2011), 3.45-3.53%/dB for Arabic (Garadat et al, 2017), 6.2 %/dB for Turkish (Durankaya et al, 2014) and 4.52-4.64%/dB for Telugu, a South Indian Dravidian language (Kumar & Mohanty, 2012). Performance on the individual lists were compared across listeners at each of the intensity levels tested using Friedman's ANOVA.…”
Section: Resultssupporting
confidence: 83%
“…The intensity at which the average score across listeners and lists was 50% was 11.64 dB above their PTA for the Afrikaans lists. The performance-intensity slope of the Afrikaans lists is similar to slope values reported for monosyllabic word lists in other languages, such as 2.8-4.2 %/dB for Spanish (Flores & Aoyama, 2008), 4.1 and 3.47%/dB for Mandarin (Han et al, 2009;Wu et al, 2011), 3.45-3.53%/dB for Arabic (Garadat et al, 2017), 6.2 %/dB for Turkish (Durankaya et al, 2014) and 4.52-4.64%/dB for Telugu, a South Indian Dravidian language (Kumar & Mohanty, 2012). Performance on the individual lists were compared across listeners at each of the intensity levels tested using Friedman's ANOVA.…”
Section: Resultssupporting
confidence: 83%
“…These words are labeled by an asterisk ( Ã ) least 96% WRS at 40 dB SL that is consistent with excellent WRS, and agrees with previous studies that reported PBmax being achieved around 30 to 40 dB supra-threshold (dB SL) in normal hearing subjects. [23][24][25]27…”
Section: Discussionmentioning
confidence: 99%
“…17 The WRS is also used in many other languages, such as Spanish, 18 Japanese, 19 Turkish, 20 and Arabic. Arabic word lists have been reported in the Egyptian, 21 Moroccan, 22 Iraqi, 23 Saudi, 24 Jordanian, 25 and other dialects. No significant differences in WRS based on ear or gender factors at the comfortable sensation level in normal hearing Jordanian subjects are reported in previous Jordanian studies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations